Islam and Democracy In Modern Indonesia: The Role of Al Washliyah in the 1955 Elections - Ja'far Ja'far; Mhd. Syahnan; Asrul Asrul (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2023)
Abstract: This article examines the role of Al Washliyah, an Islamic organization founded in Medan during the early 20th century, in the 1955 Indonesian election. This study is library research with an historical approach, drawing data from primary sources such as organizational documents and secondary sources like expert research findings. The significance of this study lies in its novel exploration of a previously unaddressed topic by researchers. This study argues that during the Old Order era, Al Washliyah accepted the concept and implementation of elections with the aim to advocate Islam as the foundation of the state. Consequently, Al Washliyah strongly supported the Masjumi Party and secured a distinctive membership within this Islamic party. Additionally, Al Washliyah engaged in political education, actively conducting training sessions in preparation for the general elections. The organization's endeavors played a pivotal role in contributing to the Masjumi Party's substantial electoral success in North Sumatra. Notably, some of its prominent figures successfully secured positions in the Constituent Assembly and the House of Representatives in Jakarta. Their involvement facilitated national-level discussions on the foundational underpinnings of the state.